LEADERSHIP ACROSS CULTURES (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2026)
Leadership is often credited (or blamed) for the success (or failure) of international operations. As with other aspects of management, leadership styles and practices that work well in one culture are not necessarily effective in another. The leadership approach commonly used by U.S. managers would not necessarily be the same as that employed in other parts of the world. Even within the same country, effective leadership tends to be very situation-specific. However, as with the other areas of international management you have studied in this text, certain leader-ship styles and practices may be more or less universally applicable and transcend international boundaries. This chapter examines some differences and similarities in leadership styles across cultures.